Penguatan Kompetensi Profesional Guru: Integrasi Pembelajaran dengan Software Matematika - Apolonia Hendrice Ramda; Bedilius Gunur (Unika Santu Paulus Ruteng, 2024)
Being a competent teacher is a big responsibility for all teachers at every level of education. Competent teacher can be realized by being adept at utilizing or using learning media that can support the achievement of learning objectives. In learning math, one of the media that can be used is geogebra Software. Geogebra Software is very interesting because it can help teachers visualize abstract concepts, especially in material related to Algebra, Calculus, Geometry, and Trigonometry. However, teachers at the secondary school level in West Cibal District have not yet recognized and used geogebra in learning. Therefore, the Community Service Team (PkM) conducted training on the utilization of geogebra Software applications in mathematics learning. This community service is expected to develop teacher competence, especially in integrating media in teaching mathematics in the classroom. This activity was facilitated by lecturers of the Mathematics Education Study Program of Unika Santu Paulus Ruteng. This activity was carried out at SMAN 1 Pagal for 2 weeks in March 2023. This community service activity was carried out in four stages, namely, planning, implementation, observation and evaluation, and reflection. Knowing the importance of this activity, the teacher gave input, namely that this training activity should be carried out regularly so that mathematics teachers can also become familiar with other mathematics Software applications. Therefore, it is hoped that more teachers will be involved in the next training activities carried out by the community service team.